One step closer to the field: visual methods in marketing and consumer research. Issue 4 (19th August 2014) - Rohani, Laila Shin; Aung, May; Rohani, Khalil
Abstract : Purpose: The purpose of this study is to examine the use of visual research methods in the area of recent marketing and consumer research. Design/methodology/approach: Content analysis was employed to investigate visual method in articles from Journal of Consumer Research (JCR), Journal of Marketing (JM), Journal of Marketing Research (JMR), Journal of Marketing Management (JMM), Consumption, Markets, and Culture (CMC), and Qualitative Market Research (QMR). Abstract, key words, and methodology sections of all articles published in these six journals from the years 2002 to 2012 were scanned to identify which of them applied visual methods in their studies. The selected articles were then closely analysed to discover how visual research methods were employed and in what manner did they contribute to the marketing and consumer behaviour discipline. Findings: This study found that a growing number of marketing and consumer researchers utilized visual methods to achieve their research goals in various approaches such as cultural inventories, projective techniques, and social artifacts. Visual method is useful when research deals with children who are not fully developed and able to comprehend text messages and also advantageous when investigating informants' metaphorical thoughts about a subject or the content of their mind. Originality/value: This paper examined how visual methods have assisted marketing and consumer researchers in achieving their goals and suggests when and how researchers can utilize the visual methods for future research.